Pengaruh penyaluran bantuan langsung tunai , beras miskin, dan subsidi LPG 3 Kg terhadap jumlah rumah tangga miskin di Kabupaten Gresik - Muhammad Zidan Izani; M Taufiq (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
The purpose of this research is to estimate the impact of direct cash assistance (BLT), rice for the poor (Raskin), and LPG subsidies on the number of poor families from 2008 to 2020 using multiple linear analytic techniques and secondary data. The results of the study conclude that what is proven to reduce the number of poor households is BLT, because the cash form of the poor can be used to improve their standard of living such as business capital, while the other two variables, namely Raskin and LPG subsidies, actually increase the number of poor households in the form of basic commodities to support daily life - days so there is minimal opportunity to improve the standard of living.